The Global Sports–Media Nexus: Reflections on the ‘Super League Saga’ in Australia - McGaughey, Sara L.; Liesch, Peter W. (Journal of Management Studies, 2002)
Despite the social and (increasingly) commercial significance of sport and sporting bodies worldwide, they remain under‐represented in the mainstream management literature. One of the more recent and dramatic examples of the global sports–media nexus is the ‘Super League saga’ in Australia. This paper recounts the tale of the Super League saga, providing a holistic analysis of the events and competitive issues arising by drawing on literatures concerning the economic nature and value of sports leagues, the resource‐based view of the firm and the nature of psychological contracts in changing environments. The analysis confirms the general monopolistic tendencies of professional sports leagues in an increasingly global industry driven by the sports–media nexus, in accord with a number of comparable cases internationally. The particular conditions of the Australian marketplace that exacerbate this tendency beyond, for example, that found in the USA, and differences in the outcomes of battles between rival leagues are also considered. The Super League saga portrays the importance of effective management of resources key to the production of the ‘rugby league product’ including, among others, the often over‐looked importance of careful management of local resources for the success of global strategies, and, where human resources are key, the importance of psychological contracting. The holistic analysis of the Super League saga in Australia affords lessons that extend well beyond the realm of sports.